Structure, cytocompatibility and biodegradation of nanocrystalline coated Mg–Ca–Zn alloys - Baigonakova, Gulsharat A.; Marchenko, Ekaterina S.; Zhukov, Ilya S.; Vorozhtsov, Alexander B. (Vacuum)
The study addresses the control of the biodegradation rate of the magnesium–zinc–calcium (Mg–Ca–Zn) alloy, and improvement of its biocorrosion resistance and cytocompatibility using titanium nitride (TiN) coating deposited by magnetron sputtering. Testing of the structure, phase and elemental composition, biocorrosion and cytocompatibility showed the efficiency of this coating technique. A corrosion-resistant biocompatible coating on the Mg alloy was developed, which comprises a dense nanostructured layer of titanium nitride 1 μm thick. The TiN coating exhibited corrosion protection for up to 4 weeks without shape loss and mass. The level of cell viability and their appearance showed a high cytocompatibility of the TiN layer.